(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Human papilloma virus (HPV) is the most prevalent virus involved in sexually transmitted diseases worldwide, and an important public health challenge for the prevention of cervical carcinoma. The present study compared the hybrid capture II assay with conventional methods for the diagnosis of HPV infection. A total of 68 women between 25-70 years of age were included in this study. Conventional methods used for diagnosis of the patients included Visible Inspection of Acetic acid (VIA), Histopathology and Pap smear tests. The hybrid Capture 2 assay was used to detect HPV DNA viral load in these patients. VIA test was performed on 66 patients. HPV DNA was detected in 8 (20.5%) of the VIA positive cases, 2 (9.5%) VIA negative, and 2 (33.3%) cases where VIA test were unsatisfactory. Pap smear test was done on 43 patients. Among them HPV DNA was detected in 13(19.1%) cases, of which 11 (37.9%) cases were Pap positive/abnormal and 2 (14.3%) were Pap negative. Out of 29 cases where histopathological examination was carried out, HPV DNA was detected in 1 (7.7%) chronic cervicitis case, 4 (66.7%) cases of CIN I, 7 (70.0%) cases of CIN II/III and invasive carcinoma. From this study it is suggested that in combination with conventional methods, hybrid Capture 2 assay is a useful tool to diagnose high-risk HPV infections when conventional tests shows apparently normal results. J. Dhaka National Med. Coll. Hos. 2014;20(01):30-34